The effects of single‐dose dexamethasone on inflammatory response and pain after uterine artery embolisation for symptomatic fibroids or adenomyosis: a randomised controlled study. (15th December 2015) - Kim, SY; Koo, B‐N; Shin, CS; Ban, M; Han, K; Kim, MD
Abstract : Objective: To investigate the effects of single‐dose intravenous dexamethasone on inflammatory responses, pain, nausea, and vomiting after uterine artery embolisation (UAE). Design: Prospective, randomised, double‐blind, and placebo‐controlled study. Setting: Tertiary‐care University centre in Korea. Population: Patients undergoing UAE for the treatment of symptomatic fibroids or adenomyosis. Methods: Patients were randomised to receive either intravenous dexamethasone (10 mg; dexamethasone group) or normal saline (control group) 1 hour before UAE. Both groups received fentanyl‐based intravenous patient‐controlled analgesia (PCA) during the 24 hours after UAE. Main outcome measures: The primary outcomes were the inflammatory and stress responses measured by white blood cell count, neutrophil percentage, C–reactive protein (CRP), interleukin–6 (IL–6), and cortisol. Secondary outcomes were severity of pain and incidence of nausea and vomiting. Results: Sixty‐four patients were enrolled and 59 patients completed the study. CRP, IL–6, and cortisol were significantly lower in the dexamethasone group compared with the control group during the 24 hours after UAE. Although the cumulative dose of fentanyl and additional analgesics administered during the 24 hours after UAE were similar between the two groups, pain scores were significantly lower in the dexamethasone group from 12 hours after UAE, and the incidence of severe nausea and vomiting was lower in the dexamethasone group. Conclusions: The administration of single‐dose intravenous dexamethasone as an adjunct to fentanyl‐based intravenous PCA is effective in reducing inflammation and pain during the first 24 hours after UAE. Tweetable abstract: Dexamethasone is effective in reducing inflammation and pain after uterine artery embolisation. Tweetable abstract: Dexamethasone is effective in reducing inflammation and pain after uterine artery embolisation.